Anaesthesia for elective inguinal hernia repair in rural Ghana - appeal for local anaesthesia in resource-poor countries - Wilhelm, Torsten; Anemana, S.; Kyamanywa, P.; Rennie, J.; Post, Stefan; Freudenberg, S. (Tropical doctor, 2006)
Local anaesthesia has been identified as the most favourable anaesthesia for elective inguinal hernia repair with respect to complication rate, cost-effectiveness, and overall patient satisfaction., Operation theatre notes in all seven hospitals in the Northern Region in Ghana over the period of 1 year were reviewed. Only 22.4% out of 1038 repairs were performed under local anaesthesia while predominantly spinal and general anaesthesia were used (48.0 and 29.6%, respectively). African surgeons chose local anaesthesia far less frequently than visiting overseas surgeons (15.6 versus 27.7%, respectively)., All surgeons in resource-poor countries should be encouraged to use local anaesthesia more frequently for elective inguinal hernia repair. Valuable resources in sub-Saharan African hospitals could be saved, especially if used in combination with outpatient surgery., The technique should be taught in teaching institutions. A simple step-by-step technique is described.